Question on Hungary: Report of the United Nations Special Representative. Fifteenth Session, Agenda Item 81, A/4606 - Héderváry, Claire de (1960)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly Sir Leslie Munroe presents to the Assembly the situation in Hungary to date: a long list of detainees and political prisoners; a "parody of justice" practiced by the regime and the fate of those who suffered it; a very limited amnesty that did not include people who participated in the uprising; political trials were mainly being conducted as secret trials where information regarding the cause of the proceedings was withheld; the Workers Councils were dissolved by December 1957 and Factory councils installed, in which only one third of the membership was elected by workers; labor courts were re-installed in workplaces with over 300 workers.